2022
DOI: 10.3389/fphar.2022.898955
|View full text |Cite
|
Sign up to set email alerts
|

A review for the pharmacological effects of paeoniflorin in the nervous system

Abstract: Paeoniflorin, a terpenoid glycoside compound extracted from Paeonia lactiflora Pall, shows preventive and therapeutic effects in various types of nervous system disorders. However, to date, no comprehensive knowledge on the pharmacological effects of paeoniflorin on the nervous system is available online. Clarification of this issue may be useful for the development of paeoniflorin as a new drug for the treatment of nervous system disorders. To this end, the authors summarize the pharmacological aspects of pae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 138 publications
0
9
0
Order By: Relevance
“…These metabolites might have more therapeutic effects on body. In addition, glycosides such as triterpenoid saponins and monoterpene glycosides in GSBXD have anti‐inflammatory, anticancer, neuroprotective and hepatoprotective activities (Bisht et al, 2022; Hong et al, 2022; Xia et al, 2017). They predominantly undergo hydroxylation to generate aglycones by glycosidic bond cleavage, which can be absorbed into blood circulation more easily and exhibits better bioavailability (He et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…These metabolites might have more therapeutic effects on body. In addition, glycosides such as triterpenoid saponins and monoterpene glycosides in GSBXD have anti‐inflammatory, anticancer, neuroprotective and hepatoprotective activities (Bisht et al, 2022; Hong et al, 2022; Xia et al, 2017). They predominantly undergo hydroxylation to generate aglycones by glycosidic bond cleavage, which can be absorbed into blood circulation more easily and exhibits better bioavailability (He et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Paeoniflorin, a terpenoid glycoside compound extracted from Paeonia lactiflora Pall, holds significant promise for treating neurological disorders, including stroke, Alzheimer's disease and PD due to its unique biological activities and pharmacological effects, which encompass antioxidative, anti‐inflammatory, autophagy regulation, enhancement of cholinergic nerve function, maintenance of ion channel homeostasis, suppression of neuronal apoptosis, and promotion of neuronal nutrition (Hong et al, 2022). In mouse models of PD induced by MPTP, rotenone or 6‐OHDA, both pretreatment and posttreatment with paeoniflorin could mitigate deficits in motor performance, α‐Syn accumulation and the loss of dopaminergic neurons through several mechanisms: (1) Inhibition of mitochondrial apoptosis by upregulating the Bcl‐2/BAD ratio and Bcl‐2/BAX ratio, downregulating cleaved caspase‐3 expression, and reducing caspase‐3/9 activities; (2) Attenuation of mitochondrial‐related oxidative stress by promoting Nrf2 nuclear translocation, leading to the activation of the Nrf2 pathway and subsequent induction of HO‐1 and SOD expression (Guo et al, 2021; Zhang et al, 2023; Zheng et al, 2017).…”
Section: Therapeutic Effects Of Natural Compounds On Pd By Modulating...mentioning
confidence: 99%
“…In mouse models of PD induced by MPTP, rotenone or 6‐OHDA, both pretreatment and posttreatment with paeoniflorin could mitigate deficits in motor performance, α‐Syn accumulation and the loss of dopaminergic neurons through several mechanisms: (1) Inhibition of mitochondrial apoptosis by upregulating the Bcl‐2/BAD ratio and Bcl‐2/BAX ratio, downregulating cleaved caspase‐3 expression, and reducing caspase‐3/9 activities; (2) Attenuation of mitochondrial‐related oxidative stress by promoting Nrf2 nuclear translocation, leading to the activation of the Nrf2 pathway and subsequent induction of HO‐1 and SOD expression (Guo et al, 2021; Zhang et al, 2023; Zheng et al, 2017). In MPP + ‐treated PC12 cells, paeoniflorin also has been shown to inhibit α‐Syn aggregation, oxidative stress and apoptosis by modulating the autophagy‐lysosome and ubiquitin‐proteasome pathways (in part by inhibiting acid‐sensing ion channels), ultimately enhancing autophagic activity (Hong et al, 2022; Sun et al, 2011). Additionally, a recent study reported that paeoniflorin significantly ameliorated bortezomib‐induced peripheral neuropathy, potentially by reducing IL‐6 expression to upregulate Parkin‐mediated mitophagy (Sun et al, 2022).…”
Section: Therapeutic Effects Of Natural Compounds On Pd By Modulating...mentioning
confidence: 99%
“…Paeoniflorin has antiinflammatory and immunomodulating [45] activities. It also has multiple therapeutic effects on nervous and [46] depressive disorders [47], as well as on liver [48], cardiovascular, and renal diseases [49].…”
Section: Pharmaceutical Information Of Nytmentioning
confidence: 99%